2019
DOI: 10.1016/j.jor.2019.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Association of eNOS 27-bp VNTR, 894G>T and 786T>C polymorphisms with susceptibility to Legg-Calve-Perthes Disease in Iranian children

Abstract: Background: The aim of this study was to analyze the association of eNOS polymorphisms with risk of Legg-Calve-Perthes Disease (LCPD). Methods: The study comprised of 45 LCPD patients and 55 controls. The eNOS polymorphisms were genotyped with PCR and by PCR-RFLP. Results: The eNOS 894G > T and −786T > C polymorphisms were significantly associated with an increased risk of LCPD. However, there was no significant association between eNOS 27-bp VNTR polymorphism and LCPD risk. Conclusion:Our results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, inflammation could play a central role in bone destruction and remodeling, leading to the appearance of LCPD as well as more severe forms of the disease [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, inflammation could play a central role in bone destruction and remodeling, leading to the appearance of LCPD as well as more severe forms of the disease [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Azarpira et al . , reported that the endothelial nitric oxide synthase (eNOS) polymorphisms 894G > T and -786 T > C increase the risk of suffering from LCPD (Table 3 ), and that the polymorphisms TNF-α -308G > A and TNF-α -238C > T could not be directly related to LCPD, but could be related to the development of osteonecrosis of the FH (Table 3 ) [ 65 , 66 ]. Furthermore, the eNOS is involved in numerous physiological processes, including angiogenesis, thrombosis, coagulation, and fibrinolysis, and, recently, the G894T mutation in the eNOS gene was described as a risk factor in LCPD (Table 3 ) [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our study did not find these variants, CBS T833C rs5742905, neither in controls nor in patients. Azarpira et al showed that the MTHFR C677T polymorphism was not associated with the risk of LCPD in Iranian children [32]. When we analyzed the results for the MTHFR C677T rs1801133 polymorphism, they did not present a significant association with the risk of susceptibility to LCPD.…”
Section: Discussionmentioning
confidence: 64%
“…Our study did not nd these variants, CBS T833C rs5742905, neither in controls nor in patients. Azarpira et al showed that the MTHFR C677T polymorphism was not associated with the risk of LCPD in Iranian children [27]. When we analyzed the results for the MTHFR C677T rs1801133 polymorphism, it did not present a signi cant association with the risk of susceptibility to LCPD.…”
Section: Discussionmentioning
confidence: 66%